Genetic and phenotypic diversity of Branchinecta sandiegonensis (Crustacea: Anostraca) in the vernal pools of Baja California, México - Arteaga, Maria Clara; Escudero, Nayeli; Gasca-Pineda, Jaime; Bello-Bedoy, Rafael; Guilliams, C. Matt (Zootaxa, 2019)
Branchinecta sandiegonensis is a passively dispersed species that occurs in the vernal pool complexes of southern California, the USA, and northwestern Baja California, México. The fragmented distribution of these vernal pool complexes could limit the gene flow, generating high genetic structure and morphometric variation across the landscape. Here we estimate the genetic and phenotypic variation of B. sandiegonensis in the southern part of its range. We sampled 15 vernal pools from four geographic regions of the Baja California Peninsula. We genotyped 150 individuals using nuclear microsatellites and 31 individuals using the mitochondrial COI region. We also conducted a morphometric analysis on a sample of 232 individuals. We found moderate levels of genetic diversity and different patterns of structure depending upon the spatial scale of analysis. Demographic models suggest contrasting trends among populations. Phenotypically, we found high levels of heterogeneity in body size of fairy shrimps within and across the regions. Our findings highlight that vernal pools in Baja California are important reservoirs of genetic and phenotypic diversity for B. sandiegonensis. The interplay between gene flow and genetic drift may have influenced the patterns we detected in the southern part of the range of this species.